Striations in an ethyl alcohol glow discharge. (March 2015) - Reyes, P G; Gómez, A; Torres, C; Martínez, H; Castillo, F; Vergara, J
Abstract: This research shows the behavior of striations in glow discharge generated with high purity ethyl alcohol at a pressure of 0.6 Torr. This paper present the number of striations as a function of the of current and voltage discharge.